Sex, Amyloid, and APOEε4 and risk of cognitive decline in preclinical Alzheimer’s disease: findings from three well-characterized cohorts - Buckley, Rachel F. (Alzheimers Dement, 2018)
INTRODUCTION: Our objective was to investigate the effect of sex on cognitive decline within the context of β-amyloid (Aβ) burden and apolipoprotein (APOE) genotype. METHODS: We analyzed sex-specific effects on Aβ-PET, APOE and rates of change on the Preclinical Alzheimer Cognitive Composite-5 (PACC-5) across three cohorts, ADNI, AIBL and HABS (n=755; clinical dementia rating (CDR)=0; Age(SD)=73.6(6.5); Female=55%). Mixed-effects models of cognitive change by sex, Aβ-PET and APOEε4 were examined with quadratic time-effects over a median of 4 years of follow-up. RESULTS: APOEε4 prevalence and Aβ burden did not differ by sex. Sex did not directly influence cognitive decline. Females with higher Aβ exhibited faster decline than males. Post-hoc contrasts suggested that females who were Aβ and APOEε4 positive declined faster than their male counterparts. DISCUSSION: Although Aβ did not differ by sex, cognitive decline was greater in females with higher Aβ. Our findings suggest sex may play a modifying role on risk of AD-related cognitive decline.